Pengawasan Pabean Melalui Sinergi Terhadap Penyelundupan Narkotika di Batam - Almahsun Misbach; Desi Albert Mamahit; Yusnaldi Yusnaldi; Pujo Widodo; Herlina Juni Risma Saragih (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
The circulation of Narcotics in Indonesia cannot be separated from the crime of Narcotics smuggling that occurred in Batam because of its strategic location in the Malacca Straits area and having access to various regions in Indonesia. Customs is an agency that oversees the entry and exit of goods from the Batam Free Trade Zone needs to continue to improve supervision of narcotics smuggling. This study aims to analyze customs supervision of Narcotics smuggling in Batam through synergy with The National Narcotics Board (BNN) as the leading sector in handling Narcotics problems in Indonesia. This paper will explore the memorandum of understanding between Customs and BNN and examine it using the theory of synergy. The method used is qualitative research with a narrative research design. The results of this study found that the synergy between Customs and BNN has been going well and supported by an agreement. Customs has the advantage of analyzing the traffic of export and import goods. This is complemented by BNN's superiority in analyzing the circulation of Narcotics in the country through intelligence activities in the form of undercover. The synergy carried out by Customs and BNN can create more effective, efficient, and sustainable supervision. Further research about other synergies is still needed to eradication of illegal circulation of Narcotics.